EFFECT OF TRIBULUS TERRESTRIS FRUIT AQUEOUS EXTRACT ON HYPERLIPIDAEMIA AND MAINTENANCE OF LIVER ARCHITECTURE IN ISOPROTERENOL-INDUCED MYOCARDIAL INFARCTION IN RATS - S. B MAHAMMAD RAHMATHULLA (International Journal of Pharma and Bio Sciences, 2013)
The present study investigates the protective effects of Tribulus terrestris Fruit aqueous Extract (TTFAEt) in myocardially infarcted rats. The oral administration of TTFAEt to rats for 40 days afforded good protection against isoproterenol-induced alterations, like Hyperlipidemia: the disorders of lipid metabolism have been ranked as one of the greatest risk factors contributing to the prevalence and severity of atherosclerosis, stroke and coronary heart diseases. Cardiac levels of lipid peroxidation (LPO) as well as the activities of antioxidant enzymes like Superoxide dismutase (SOD), Catalase (CAT), glutathione peroxidase (GPx), Glutathione-S-transferase (GST). Antioxidants can prevent reactive oxygen species-mediated damage and thus may have potential application in the prevention and cure of such diseases. Myocardial infarction produces a significant abnormal liver functioning. Liver tissue marker enzymes like alanine aminotransferase (ALT), aspartate aminotransferase (AST) and lactate dehydrogenase (LDH). The protective effect of TTFAEt was further supported by the reversal of isoproterenol-induced histological changes in the liver. The results suggest that TTFAEt protect the heart and circulatory system and also hepatoprotective and thereby maintain the near normal architecture of liver tissue.